THE ROLE OF COMMUNICATIVE LANGUAGE TEACHING METHOD IN ENGLISH LANGUAGE LEARNING - Jabbarov, Ulugbek (Журнал иностранных языков и лингвистики, 2023)
Communicative language teaching makes use of real-life situations that necessitate communication. The teacher sets up a situation that students are likely to encounter in real life. Unlike the audiolingual method of language teaching, which relies on repetition and drills, the communicative approach can leave students in suspense as to the outcome of a class exercise, which will vary according to their reactions and responses. The real-life simulations change from day to day. Students’ motivation to learn comes from their desire to communicate in meaningful ways about meaningful topics.